2018
DOI: 10.1016/j.jacep.2017.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Reverse Remodeling Using Electrocardiogram Fusion-Optimized Intervals in Cardiac Resynchronization Therapy

Abstract: Device optimization based on FOI achieves greater LV remodeling, compared with nominal settings. (ECG Optimization of CRT: Evaluation of Mid-Term Response [BEST]; NCT01439529).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
84
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(89 citation statements)
references
References 34 publications
2
84
0
3
Order By: Relevance
“…None of the patients had QRS widening or worsening in the LVEF or MR at 6 months after continuous CRT optimization using the SyncAV algorithm. Trucco et al 21 showed that baseline manual optimization of the AV and ventriculo-ventricular delays, to achieve biventricular fusion pacing, immediately postimplantation leads to a greater proportion of patients achieving both electrical synchrony and LV reverse remodelling at 12 months. Our study validates the long-term effect of an automated continuously optimized biventricular fusion-pacing algorithm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…None of the patients had QRS widening or worsening in the LVEF or MR at 6 months after continuous CRT optimization using the SyncAV algorithm. Trucco et al 21 showed that baseline manual optimization of the AV and ventriculo-ventricular delays, to achieve biventricular fusion pacing, immediately postimplantation leads to a greater proportion of patients achieving both electrical synchrony and LV reverse remodelling at 12 months. Our study validates the long-term effect of an automated continuously optimized biventricular fusion-pacing algorithm.…”
Section: Discussionmentioning
confidence: 99%
“…22 Even in studies that used an ECG-based optimization, the ECG analyses were performed with a paper speed between 50 and 300 mm/s, used computerized recording systems, and required experienced observers for QRS width measurement. 12,21 In contrast, we used the standard 12-lead surface ECG at a regular speed of 25 mm/s with automated measurements, which are faster, accurate, and easily reproducible.…”
Section: Discussionmentioning
confidence: 99%
“…Narrowing of the QRS complex after CRT reflects the improvement in electrical synchrony. A reduction in QRS duration after CRT has been shown to acutely improve hemodynamics and as well as left ventricular reverse remodeling . In addition, narrowing of the QRS has been associated with a reduction in functional mitral regurgitation as well as a reduction in cardiovascular hospitalizations and mortality .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, symptomatic heart failure patients with reduced ejection fraction (HF r EF) with prolonged QRS duration is indicated for cardiac resynchronization therapy (CRT) based on various international guideline . CRT reduces mortality and HF hospitalizations in selected patients with left ventricular (LV) systolic dysfunction and prolonged QRS duration …”
Section: Introductionmentioning
confidence: 99%